2007
DOI: 10.1007/s11096-007-9161-8
|View full text |Cite
|
Sign up to set email alerts
|

Recall of drug utilization depends on subtle structural questionnaire characteristics

Abstract: The structure of the questionnaire used to collect self-reported information about antimalarial treatments influences the recall, even when close ended questions asking for specific drugs are used. Among subjects having been treated for malaria more than once, the first antimalarial drugs being asked were more likely to be selected.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
16
0

Year Published

2008
2008
2019
2019

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 12 publications
(17 citation statements)
references
References 16 publications
1
16
0
Order By: Relevance
“…This is consistent with previous finding in studies addressing the effect of questionnaire design on the recall of pharmacological treatments [16,18,19]. …”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…This is consistent with previous finding in studies addressing the effect of questionnaire design on the recall of pharmacological treatments [16,18,19]. …”
Section: Discussionsupporting
confidence: 93%
“…This sample allows differences in the estimates of the two questionnaires to be detected with a power of 80%, for a 95% confidence level, when the magnitude of the difference corresponds to a risk ratio of two, and the proportion of drug use is above 10%, considering a design effect as high as 1.15 (which would be obtained for an average cluster size of 15 and an intra-cluster correlation coefficient of 0.01) [15]. The assumptions about the expected design effect and average cluster size are supported by a previous similar study in the same setting [16]. …”
Section: Methodsmentioning
confidence: 66%
“…That study also showed similar results for documented clinic attendances, antimalarial prescriptions, and antibiotic prescriptions. Furthermore, differences in questionnaire design may also influence the results for recall of past health events; a study of antimalarial drug utilization recall conducted in Mozambique indicated that recall of which antimalarial drug was used to treat a past episode of malaria could be influenced by the ordering of the drugs as read to the respondent [19].…”
Section: Discussionmentioning
confidence: 99%
“…In the majority of cases, the questionnaires are based on recall questions regarding drug use, requiring short, medium or even long-term memory recall from the respondent 1,[3][4][5] . Under-reporting of drug use is considered to result from recall error, even if the error magnitude is not known [6][7][8][9][10][11] .…”
Section: Introductionmentioning
confidence: 99%
“…Each author adopts a preferred period based on convenience or on a trend observed in other studies 13 . This practice may hinder the comparison of estimates of drug use prevalence obtained in different studies 5,12,14,15 . Studies evaluating the recall period and validity of the collected data are scarce.…”
Section: Introductionmentioning
confidence: 99%